2012
DOI: 10.3390/medicina48100075
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PAI-1 Gene Promoter-675 (4G/5G) Polymorphism on Fibrinolytic Activity After Cardiac Surgery Employing Cardiopulmonary Bypass

Abstract: Background and Objective. The plasminogen activator inhibitor type-1 (PAI-1) gene promoter contains 675 (4G/5G) polymorphism. The aim of this study was evaluate the effect of the PAI-1 promoter-675 (4G/5G) polymorphism on the concentrations of PAI-1 and tissue plasminogen activator/PAI-1 (t-PA/PAI-1) complex and bleeding volume after on-pump cardiac surgery.Material and Methods. A total of 90 patients were included in the study at Pauls Stradins Clinical University Hospital. Seven patients were excluded due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The promoter regions 675 4Guanine/5Guanine (4G/5G) and −844 Adenosine/Guanine (A/G) polymorphisms, both affecting the fibrinolytic balance, are two of the most common. Reassessing blood from the latter study [ 9 ], we recently confirmed the findings of other investigators that in addition to decreased plasma levels of PAI-1, excessive bleeding after CPB was associated with PAI-1 -675 5G/5G polymorphism [ 5 , 10 14 ].…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…The promoter regions 675 4Guanine/5Guanine (4G/5G) and −844 Adenosine/Guanine (A/G) polymorphisms, both affecting the fibrinolytic balance, are two of the most common. Reassessing blood from the latter study [ 9 ], we recently confirmed the findings of other investigators that in addition to decreased plasma levels of PAI-1, excessive bleeding after CPB was associated with PAI-1 -675 5G/5G polymorphism [ 5 , 10 14 ].…”
Section: Introductionsupporting
confidence: 83%
“…Postoperative bleeding volumes were recorded as chest tube drainage (CTD) in mL at 4 and 24 h after the surgery [ 9 ]. Inclusion and exclusion criteria, as well as perioperative management, postoperative bleeding and demographic and laboratory data were the same as published before [ 9 ] and genomic DNA was extracted as reported by Ozolina et al [ 14 ]. Here, we only describe the methods used for analysis of PAI-1 -844 A/G and ACE Intron 16 I/D polymorphisms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation